Effect of dynamic evolution of misfit dislocation pattern on dislocation nucleation and shear sliding at semi-coherent bimetal interfaces. (15th January 2018) - Chen, X.Y.; Kong, X.F.; Misra, A.; Legut, D.; Yao, B.N.; Germann, T.C.; Zhang, R.F.
Abstract: Misfit dislocation pattern is generally accepted to play a critical role on the interface mediated deformation mechanism such as dislocation nucleation and shear sliding in various flat interfaces, however, a specific mechanical loading may dynamically modify its distribution and character before the appearance of distinct plastic flow out of interfaces. Taking bimetal semi-coherent interfaces with high symmetrically distributed misfit dislocations as an illustration, we reveal for the first time that the dynamic evolution of misfit dislocation patterns in interface appears for some specific interface types and loading schemes, and eventually governs the preferred sites of dislocation nucleation and the shear sliding mechanism. In contrary to the nearly unchanged feature of misfit dislocations under biaxial in-plane tension, the initial patterns around nodes of misfit dislocations are found to be distorted and spread anisotropically within interface during uniaxial in-plane loading, which in turn governs the non-Schmid phenomena of dislocation nucleation. A similar dependence of shear sliding mechanism on the anisotropic feature of core spreading of misfit dislocations in interface is also observed, depending on the characteristic of misfit dislocation patterns. Further investigations suggest that the dynamic evolution of misfit dislocation patterns may differ substantially for different types of interfaces, and consequently contribute to different mechanisms of dislocation nucleation and shear sliding. These results suggest a necessity to investigate the dynamic evolution of misfit dislocation patterns to get a more realistic understanding on the interface dominated plasticity. Graphical abstract: Image 1